Big Data Research for Diabetes-Related Diseases Using the Korean National Health Information Database - Kyung-Soo Kim; Bongseong Kim; Kyungdo Han (Diabetes & Metabolism Journal)
The Korean National Health Information Database (NHID), which contains nationwide real-world claims data including sociodemographic data, health care utilization data, health screening data, and healthcare provider information, is a powerful resource to test various hypotheses. It is also longitudinal in nature due to the recommended health checkup every 2 years and is appropriate for long-term follow-up study as well as evaluating the relationships between health outcomes and changes in parameters such as lifestyle factors, anthropometric measurements, and laboratory results. However, because these data are not collected for research purposes, precise operational definitions of diseases are required to facilitate big data analysis using the Korean NHID. In this review, we describe the characteristics of the Korean NHID, operational definitions of diseases used for research related to diabetes, and introduce representative research for diabetes-related diseases using the Korean NHID.